Fundoscopic Findings in Pregnancy Related Hypertensive Disorders and Its Association with Maternal and Fetal Outcomes - Nazia Fakhir, Saadia Shamsher, Fauzia Anbreen, Reema Fateh (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the prevalence of retinal changes in pregnancy-related hypertensive disorders and their association with maternal and fetal outcomes. Introduction: There is a grave risk to both mother and child when hypertensive problems complicate pregnancy. However, hypertensive sort of disorders during pregnancy have been allied to poor maternal and also neonatal outcomes. This research aimed to evaluate effects of hypertensive sort of disorders of pregnancy on both mothers and their unborn children by analyzing the prevalence, causes, and treatment of these conditions. Subjects and methods: BBH Rawalpindi, Inpatient Department of Gynecology and Obstetrics conducted the case-control research during the period from January 2021 to June 2021. In all, 149 patients participated in the research. Because seven patients could not be located, 142 cases were analyzed. Mild class preeclampsia (65.0 instances), severe class preeclampsia (32.0 hot cases), and also eclampsia (one case) were the subcategories used to categorize patients further, according to research. Thirty-one women who were not hypertensive throughout pregnancy were enlisted as controls. Results: Ninety percent of cases manifested with some edema. About a quarter basically patients had proteinuria above 300.0 mg/24 hours (26.76%), nearly half had proteinuria over two g/24 hours (47.18%), and about a quarter had urine protein based excretion of 3.0-5.0 g/24 hours (25.35%). Usually, incidence of specially HELLP (normally hemolysis, increased liver based special enzymes, and also squat platelet tot up) set of symptoms was 2.80%, raised bilirubin levels were seen in 47%, illustration symptoms occurred in 6.4%, vaginal based hemorrhage occurred in 11.30%, in addition to 42.2% of cases involved the central nervous system. It was shown that eclampsia was the cause of mortality in 2.8% of all maternal deaths. 16.9 percent of births were stillbirths, while 4.23 percent of newborns died. Conclusion: Compared to pregnant women with normal blood pressure, those who suffer from hypertensive disorders of pregnancy have a higher risk of having a baby born with complications. Our research did find a declining trend, although it was less than those seen in other studies; this may be because more of our study’s births occurred in hospitals. Keywords: Neonatal outcome, maternal outcome, acute renal failure, and the HELLP syndrome